The Effects of Wushu Training on Physical Fitness in Chinese Adolescents - Dongyang, Zhu; Hengsuko, Ekasak; Promthep, Kreeta; Wiangthongsarat, Onsuda (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study was to study the effects of Chinese Wushu martial arts training. It affects two aspects of physical performance : Cardiovascular endurance and Muscle strength using experimental research. The population used in the research is students of Henan Mechanical and Electrical Vocational College and use specific random sampling. The sample consisted of 150 people, divided into 75 male and 75 female students. The research instrument was wushu training program for 8 consecutive weeks. Using 8 weeks of training, testing the cardiovascular endurance and muscle strength from running 1000 meters for men and running 800 meters for women and testing 60s sit ups before training and after training 8 weeks. The effects of wushu training on cardiovascular endurance and muscle strength of college students were analyzed by using mean and independent sample t-testing and the results found that: The results show that: 1. The gender and height of college volunteers had no significant influence on the endurance and strength of college students comparing before and after the training 8 week there were no statistically significant differences. 2. There was a statistically significant increase in cardiovascular endurancefrom running 1000 meters for men and running 800 meters for womens test at 0.01 when comparing before and after the 8 weeks of training. 3. There was a statistically significant increase in muscle strength from the 60s sit ups test at 0.01 when comparing before and after the 8 weeks of training.